Transgenic food: impacts on human and environmental health (Research, Society and Development, 2022)
Transgenics and “Genetically Modified Organisms” (GMO) are organisms that received, through artificial techniques in laboratory, genes from another donor organism. The need of information and clarification about the subject brought the objection to discuss concepts, to analyze the marketing and labelling’s law and the impacts caused by the production of this type of food, mostly in Brazil, one of the biggest producers of trangenic food in the world. The study, made by secondary sources, highlights positives and negatives aspects from the generation and use of the transgenics in daily life, considering the connection that they have with the use of pesticides that affects human’s health and the environment. Concludes that both sides, those who reject, and those who defend the reality brought up by biotecnology, have your agument valid in this long ‘battle’ which envolves the controversial subject, therefore the lacking of transparency and dissemination of infrormation about these food.